KETERHUBUNGAN GALOIS FIELD DAN LAPANGAN PEMISAH - Irawanto, Bambang (MATEMATIKA, 2001)
﻿﻿﻿In this paper, it was learned of the necessary and sufficient condition for finite field with pn elements, p prime and n ³ 1 an integer. A field F is an extention field of a field K if K subfield F. The extension field F of field K is Splitting field of collection polinomial { fi (x) | i Î I } of K if F smallest subfield containing K and all the zeros in of the polinomial fi(x). The zeros of polinomial fi(x) are elements of field F and the elements of F is finite then F is finite field (Galois fileld). F is finite with pn elements, p prime and n ³ 1 an integer if only if F is Splitting field of  - x over Zp.